The shield of the screen: The role of anger on the development of social media addiction and internet gaming disorder - Fiammetta Iannuzzo; Clara Lombardo; Maria Catena Silvestri; Fabrizio Turiaco; Giovanni Genovese; Caterina Rombolà; Carmela Mento; Maria Rosaria Anna Muscatello; Antonio Bruno (AIMS Public Health)
This study aims to explore if the dimensions of anger can be risk factors for the development of social media addiction and an internet gaming disorder, considering that the correlation between anger and these specific subcategories of internet addiction can represent a core intervention in their prevention and treatment. 477 subjects, recruited among the general population, were assessed on-line by the following tools: STAXI–2; BSMAS, and IGDS9–SF. A correlation analyses showed a significantly positive relationship between the total score of the BSMAS and the STAXI–2 scales SANG (p < 0.0001), TANG (p < 0.0001), AX–O (p = 0.003), and AX–I (p < 0.0001), and between the total score of the IGDS9–SF and the STAXI–2 scales SANG (p = 0.002), TANG (p < 0.0001), AX–O (p = 0.001), AX–I (p < 0.0001), and AC–O (p = 0.004). A linear regression model showed how TANG and AX–I were direct predictors of the BSMAS total scores, and how AX–I was a direct predictor of the IGDS9–SF total scores. It appears plausible that there is a significant correlation between the dimensions of anger and the emergence of social media addiction and internet gaming: internet usage may serve as a coping mechanism for emotional or social challenges and as a protective screen to deal with negative emotions.